1999
DOI: 10.1002/(sici)1097-4555(199911)30:11<1027::aid-jrs442>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of poly(2-pyridinium hydrochloride-2-pyridylacetylene)

Abstract: Poly(2-pyridinium hydrochloride-2-pyridylacetylene) (P2EPH) is a water-soluble conjugated polymer that is fluorescent when excited in the visible region. The problems associated with this fluorescence have been overcome, thus permitting a Raman spectroscopic investigation of P2EPH. The fluorescence was avoided by recording spectra with excitation in the UV region (244 nm); for spectra excited with a visible laser, silver colloids, electrodes and pellets were used to minimize the fluorescent background. The obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…By exciting the outermost layer of human skin and nail at 632.8 nm, De Faria and Souza [1] could photobleach initially strong fluorescent background and reject the residual emission by spatial filtering. Millen et al [2] recorded the Raman spectra of poly(2-pyridinium hydrochloride-2-pyridylacetylene) in the UV region (244 nm) to avoid fluorescence. In order to reduce the fluorescence intensity, Pelletier and Altkorn [3] collected Raman spectra in liquid-core optical fiber waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…By exciting the outermost layer of human skin and nail at 632.8 nm, De Faria and Souza [1] could photobleach initially strong fluorescent background and reject the residual emission by spatial filtering. Millen et al [2] recorded the Raman spectra of poly(2-pyridinium hydrochloride-2-pyridylacetylene) in the UV region (244 nm) to avoid fluorescence. In order to reduce the fluorescence intensity, Pelletier and Altkorn [3] collected Raman spectra in liquid-core optical fiber waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…The problems associated with this fluorescence were first overcome by Batchelder et al 7 for water-soluble poly-(2-pyridinium hydrochloride-2-pyridylacetylene) (P2EPH). Two pathways towards overcoming this problem were used: (i) measurements of Raman spectra in the resonance region and (ii) utilization of surface-enhanced Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that the enhancement mechanism is essentially electromagnetic and the vibrational modes are not strongly affected by the metal surface. 7 The vibrational assignment was also presented. 7,9 The frequencies of some vibrational modes assigned to polyacetylenic chain vibrations showed a dependence on the energy of the exciting radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental approaches to background/baseline correction are not suitable here. [29][30][31][32][33][34] A chemometric approach (of which there are many) was preferred because this could be more easily implemented on conventional Raman systems. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Morphological weighted penalized least squares (MPLS) 49 was used for baseline correction of Raman spectra because of its inherent simplicity, combined with its flexibility, suitability for automation, and effectiveness at mitigating baseline artefacts.…”
Section: Resultsmentioning
confidence: 99%